The effect of a dentifrice containing zinc citrate and Triclosan on developing gingivitis - Saxton, C A; van der Ouderaa, F J (Journal of periodontal research, 1989)
A partial mouth experimental gingivitis model was employed to establish the potential efficacy of a dentifrice containing a zinc salt and the antimicrobial agent Triclosan to prevent or delay the development of gingivitis over a period of 28 days. Initially, gingival health was established in 34 subjects following a 6-week period of professional tooth cleaning and oral hygiene instruction. A toothshield was constructed to fit 4 posterior mandibular teeth. Undiluted test or placebo dentifrice was applied to the experimental teeth via the toothshield, which also prevented plaque removal from these teeth during habitual brushing of the remainder of the dentition. The presence of plaque, bleeding after probing and visual signs of inflammation were independently assessed. Plaque accumulated rapidly and gingivitis developed in both groups. At the 2-wk assessments, lower mean plaque scores were recorded for the group using the test dentifrice. At the 4-wk assessment a significantly lower level of gingivitis was recorded for the test group. It is concluded that (a) the model can be used to establish the potential efficacy of a dentifrice to maintain gingival health, (b) the dentifrice containing zinc citrate and Triclosan was efficacious and (c) the Gingival Index possibly overestimates the proportion of healthy gingival sites.